Analysis of banquet section performance during high season at the UTC Hotel Semarang - Artin Bayu Mukti; Azis Nur Rosyid (Surya Hijau Manfaat, 2023)
This research was conducted to find out how the banquet section performance during high season at UTC Hotel Semarang. The analytical method used in this study is Qualitative description of the method of collecting data through 4 ways, namely, interviews, observations, questionnaires and literature. The results of data analysis stated that the banquet operations went smoothly. While the obstacles faced by the banquet section are the limitations of Human Resources. The performance of the banquet staff at the time of the high season is good and maximum.